Analysis Based on Arduino Uno Producing a Baracuda Smoking Tool With a Smoke Concentration and Temperature Monitoring System - Oktalia Triananda Lovita; Khairuman; Zharifah Muthiah; Rossiana Ginting (LPPM Politeknik Aceh Selatan, 2025)
A smoked barracuda fish product smoking device with closed circulation using a temperature monitoring system and smoke concentration based on Arduino Uno has been created. The design of the cold smoking device is divided into three parts, namely the combustion area, the smoke pipe, and the smoking chamber. Smoke drift of (25.53%-32.45)%. The average length of the fish was 16.7 cm and the average weight of the barracuda fish was 192.3 grams. 10 barracuda fish were put into the smoking room. The lowest water content value for smoked barracuda fish, namely 25.53%, occurred at a smoking time of 6 hours and the highest water content for smoked barracuda fish, namely 32.45%, occurred at a smoking time of 3 hours. The efficiency of the time needed to smoke mackerel on the water content was 6 hours compared to a smoking time of 3 hours. This means that the longer the smoking, the lower the water content value in smoked mackerel.